Elementos do teatro no ensino de língua inglesa em escolas públicas estaduais - Setti, Tassia Raffo (2016)
This work is a bibliographic research on the increased motivation of teachers and students from the insertion of theater elements when teaching/learning English in public schools. In light of Vygotsky (2003), we seek to understand the importance of play activities in the development of children and adults. We also aim to learn what obstacles of public education the methods that include the use of theater in the classroom can overcome. Therefore, we collect several reports from teachers of modern languages who have had this type of experience. It is intended to motivate English-speaking teachers to experience methodologies based on theater in the classroom, since we believe in the effectiveness.